2006
DOI: 10.1111/j.1469-8749.2006.02027a.x
|View full text |Cite
|
Sign up to set email alerts
|

Gross motor abilities in children with Hurler syndrome

Abstract: Hurler syndrome is the most severe form of mucopolysaccharidosis type I. There is a paucity of literature reporting the gross motor abilities of children with untreated Hurler syndrome. The purpose of this case series is to describe the gross motor abilities of one male and three female children (mean age 11.4mo [SD 3.1]; range 9.5–16mo) diagnosed with Hurler syndrome. The children were assessed using the Peabody Developmental Motor Scales, 2nd edition. Gross motor delays were present in all four children at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…A study of South‐American MPS II patients [Schwartz et al, 2007] showed that early clinical manifestations of patients with the severe form were usually language and motor development delay. MPS I was the second group with most reports of developmental delay before diagnosis was established, mostly regarding speech, and this is in accordance with the literature [Conway et al, 2005; Dusing et al, 2006]. MPS IVA and MPS VI were the groups with fewer reports of delayed development, as expected, since these subtypes of MPS usually do not show cognitive impairment [Neufeld and Muenzer, 2001].…”
Section: Discussionsupporting
confidence: 85%
“…A study of South‐American MPS II patients [Schwartz et al, 2007] showed that early clinical manifestations of patients with the severe form were usually language and motor development delay. MPS I was the second group with most reports of developmental delay before diagnosis was established, mostly regarding speech, and this is in accordance with the literature [Conway et al, 2005; Dusing et al, 2006]. MPS IVA and MPS VI were the groups with fewer reports of delayed development, as expected, since these subtypes of MPS usually do not show cognitive impairment [Neufeld and Muenzer, 2001].…”
Section: Discussionsupporting
confidence: 85%
“…Children with Hurler syndrome have been documented to have delayed gross motor abilities both before 4 and immediately after UCBT (Dr Dusing, unpublished data, 2005). Locomotor abilities such as transitioning between positions, creeping, walking, running, and jumping have been the most delayed based on previous research using the Peabody Developmental Motor Scales, second edition.…”
Section: Discussionmentioning
confidence: 96%
“…3 In a previously published case series, including one of the subjects included in this study, we documented gross motor abilities that were below average as early as 10 months of age. 4 Children with untreated Hurler syndrome may never gain the ability to ambulate or may lose this ability as their symptoms progress.…”
mentioning
confidence: 99%
“…These children had marked deficits in gross motor abilities, similar to children assessed prior to transplantation. 6 However, the description of gross motor development for this population was oversimplified by using the GMQ. The children with Hurler syndrome were gaining new abilities at different rates on each gross motor subtest (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Gross motor abilities are reported to be limited in children with Hurler syndrome who have not received medical intervention and in some who have undergone a bone marrow transplant. [4][5][6] Dusing et al 6 described the gross motor abilities and joint range of motion of 4 children (aged 9.5-16 months) with Hurler syndrome, 2 of whom were included in the sample for the current study. All 4 children had limitations in joint range of motion and had gross motor abilities that were below average on the Peabody Developmental Motor Scales, second edition (PDMS-2), 7 prior to any form of transplantation.…”
mentioning
confidence: 99%